The fusion of tradition and modernity: a study on the development of Hunan Flower Drum Opera from the perspective of "living heritage" - Liao, Yifu (Journal of Ecohumanism, 2024)
Hunan Flower Drum Opera is a treasure of Chinese local opera, occupying an important position in the history of Chinese opera development with its unique artistic charm and profound cultural heritage. However, in the face of the rapid changes in modern society, Hunan Flower Drum Opera is facing many challenges, such as the discontinuity of inheritance, the loss of audiences, and the lack of innovation. Based on the theoretical perspective of "living inheritance" and the development of Hunan Flower Drum Opera, this paper uses methods such as literature analysis, field research, and in-depth interviews to analyse the difficulties faced by the inheritance and development of Hunan Flower Drum Opera. The research shows that in order to achieve sustainable development, Hunan Flower Drum Opera must be based on tradition and oriented towards the modern world, and transform and upgrade itself through inheritance and innovation. Specifically, it is necessary to strengthen theoretical research and deepen the connotation of "living inheritance"; innovate performance forms and enhance artistic taste; expand communication channels and cultivate new audiences; improve the talent training system and stimulate endogenous motivation for inheritance; and strengthen policy support and create a good environment for development. This study aims to provide theoretical inspiration and practical guidance for the inheritance and development of Hunan Flower Drum Opera and other traditional opera arts, and to provide useful reference for the creative transformation and innovative development of traditional culture in the modern context.